2004
DOI: 10.1038/sj.npp.1300535
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions between Cannabinoids and Environmental Stress in the Activation of the Central Amygdala

Abstract: Anxiety and panic are the most common adverse effects of cannabis intoxication; reactions potentiated by stress. Data suggest that cannabinoid (CB 1 ) receptor modulation of amygdalar activity contributes to these phenomena. Using Fos as a marker, we tested the hypothesis that environmental stress and CB 1 cannabinoid receptor activity interact in the regulation of amygdalar activation in male mice. Both 30 min of restraint and CB 1 receptor agonist treatment (D 9 -tetrahydrocannabinol (2.5 mg/kg) or CP55940 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
100
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 48 publications
(73 reference statements)
15
100
1
Order By: Relevance
“…Thus, cannabinoid activation in the BLA acts to modulate the effects of stress on conditioning and extinction. In support, Patel et al (2005) found a synergistic interaction between environmental stress and CB 1 receptor activation in the amygdala, because the combination of restraint stress and CB 1 agonist administration produces robust Fos induction within the BLA and the central amygdala.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, cannabinoid activation in the BLA acts to modulate the effects of stress on conditioning and extinction. In support, Patel et al (2005) found a synergistic interaction between environmental stress and CB 1 receptor activation in the amygdala, because the combination of restraint stress and CB 1 agonist administration produces robust Fos induction within the BLA and the central amygdala.…”
Section: Discussionmentioning
confidence: 58%
“…First, stressful stimuli affect anandamide mobilization in brain regions that are involved in the control of emotions. In rats, for example, an electric shock to the paw elevates anandamide levels in the midbrain (33), whereas in mice, physical restraint decreases anandamide levels in the amygdala (34). Second, pharmacological blockade or genetic ablation of CB 1 receptors exacerbates normal reactions to acute stress, presumably by disabling an endocannabinoid modulation of these reactions (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Other markers of neuronal activity, such as phosphorylation of kinases, may better reflect differences in freezing behavior (in particular if analyzed in the absence of injection stress in CB1-KO and CB1-WT mice) (Cannich et al, 2004). Previous studies reported an increase in Fos-ir in the central amygdala of naive mice following pharmacological blockade of CB1 (Patel et al, 2005a). In addition, CB1 plays a complex role in the regulation of fear and anxiety within the medial prefrontal cortex (Lin et al, 2009), and neuronal activity within the prelimbic cortex seems to directly Figure 6.…”
Section: Discussionmentioning
confidence: 99%